2010
DOI: 10.2519/jospt.2010.3345
|View full text |Cite
|
Sign up to set email alerts
|

A Progressive 5-Week Exercise Therapy Program Leads to Significant Improvement in Knee Function Early After Anterior Cruciate Ligament Injury

Abstract: STUDY DESIGN Prospective cohort study without a control group. OBJECTIVES Firstly, to present our 5-week progressive exercise therapy program in the early stage after anterior cruciate ligament (ACL) injury. Secondly, to evaluate changes in knee function after completion of the program for patients with ACL injury in general and also when classified as potential copers or noncopers, and, finally, to examine potential adverse events. BACKGROUND Few studies concerning early-stage ACL rehabilitation protocols… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
197
4
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 206 publications
(215 citation statements)
references
References 67 publications
3
197
4
11
Order By: Relevance
“…The selected results obtained in a postsurgical period led to a conclusion that implementing physiotherapy prior to the ACL reconstruction is a beneficial procedure in a complex therapy programme [28]. It is also confirmed by several other authors [38][39][40]. The study by Swank et al is one of the works in which the authors revealed a significant value of prehabilitation for the treatment of knee joint diseases [39].…”
Section: Dyskusjasupporting
confidence: 54%
See 3 more Smart Citations
“…The selected results obtained in a postsurgical period led to a conclusion that implementing physiotherapy prior to the ACL reconstruction is a beneficial procedure in a complex therapy programme [28]. It is also confirmed by several other authors [38][39][40]. The study by Swank et al is one of the works in which the authors revealed a significant value of prehabilitation for the treatment of knee joint diseases [39].…”
Section: Dyskusjasupporting
confidence: 54%
“…Badania oceniające rolę rehabilitacji przedoperacyjnej chorych z dysfunkcjami stawu kolanowego (w tym z całkowitym uszkodzeniem ACL), które przeprowadzili Shaarani [38], Swank [39] i Eitzen [40] oraz dotychczasowe doświadczenia autora pracy [22] wskazują na konieczność poszukiwania dowodów na potwierdzenie tezy, iż fizjoterapia w tym okresie jest równie ważna, jak po operacji.…”
Section: Wstępunclassified
See 2 more Smart Citations
“…In this phase, we also initiated core stabilization exercises with dorsal, lateral and ventral bridges 15 and sensorimotor training recommended by the University of Delaware [16][17][18] . This phase consisted of 10 gradually progressed sessions and at the end the patient had no pain and effusion, did not report any episode of giving way and reached maximum muscle function (5/5) for flexion and knee extension.…”
Section: Interventionmentioning
confidence: 99%